SURVIVAL AMIDST COVID-19 PANDEMIC: CONTRIBUTIONS OF THE FOREST TO THE LIVES OF THE FILIPINOS - John Louie M Bona; Kim Vincent M Timbal; Jaypee D Bangate; Michelle A Resueño; Ericson Esquibel Coracero; RB Juarez Gallego (Indonesian Journal of Forestry Research, 2023)
COVID 19 has brought significant damages to the lives of the people due to extremely long lockdowns and unemployment. Thus, leaving no choice to the residents but to depend their survival on what is available in the environment. This study was conducted to assess the contribution of the forests to the lives of the locals in Aurora through a survey on 161 respondents. Data were analyzed through descriptive statistics like frequency, mean, rank, and percentage. Results showed that 100% of the respondents depends on the forests for their food which includes fruits and vegetables in the wild and in their farms situated in the along and in the forest. Meanwhile, 116 individuals (72%) obtained livelihood from the forest in times of the pandemic in the form of labor, farming, selling of forest goods, charcoal making, and furniture making. Generally, the individual income obtained from forest livelihood ranged from Php500.00 to Php25,000.00 and an overall mean individual monthly income of Php4,084.19. Each type of livelihood activities provided a mean monthly income ranging from Php 4350 to Php 9021 per person. However, the respondents faced challenges such as loss of products due to theft, competition among those with the same livelihood due to limited number of consumers, and struggles concerning the health of the workers especially the elders, disabled, and other high-risk individuals to COVID-19. The government must consider providing needs (financial, technical, knowledge) to the locals in obtaining products and services from the forest for a sustainable utilization of the resources.